Overexpression of Galectin-3 in Chronic Lymphocytic Leukemia Is Associated With 17p Deletion: A Short Report - Michalová, Zuzana; Čoma, Matúš; Kičová, Miroslava; Gabzdilová, Juliana; Dedinská, Kinga; Guman, Tomáš; Hájiková, Martina; Veselinyová, Dominika; Giertlova, Mária; Gál, Peter; Šarišský, Marek (Anticancer research, 2019)
BACKGROUND/AIM: Galectins belong to the family of galactose-binding proteins known to play an important role in the processes of cell proliferation, differentiation, migration and neoplastic progression. Herein, we studied the expression of galectin-3 (Gal-3) in chronic lymphocytic leukemia (CLL). MATERIALS AND METHODS: The expression of Gal-3 was analyzed by means of multiparametric flow cytometry in normal and pathological B-cells from peripheral blood and bone marrow samples of 67 patients with CLL. RESULTS: Pathological B-cells expressed significantly higher levels of cytoplasmic Gal-3 than normal B-cells. Moreover, overexpression of cytoplasmic Gal-3 was observed in the prognostically poorest subgroup of CLL patients, namely those with 17p deletion. CONCLUSION: Our results indicate a possible role of galectin-3 in CLL pathophysiology and its potential value as a prognostic marker and therapeutic target.
Keywords: senioři; lidské chromozomy, pár 17; galektiny; Up-Regulation; galektin 3; senioři nad 80 let; Galectin-3; krevní proteiny; upregulace; Prognosis; regulace genové exprese u nádorů; Chromosomes, Human, Pair 17; Blood Proteins; Middle Aged; mužské pohlaví; Galectins; Adult; Biomarkers, Tumor; Aged, 80 and over; chronická lymfatická leukemie; cytoplazma; nádorové biomarkery; ženské pohlaví; chromozomální delece; prognóza; Gene Expression Regulation, Neoplastic; Humans; Leukemia, Lymphocytic, Chronic, B-Cell; chronic lymphocytic leukemia; 17p deletion; lidé středního věku; Galectin 3; B-cells; Chromosome Deletion; cytogenetics; Cytoplasm; flow cytometry; dospělí; Female; Aged; lidé; Male